Advanced applications of sustainable and biological nano-polymers in agricultural production - Vinzant, Kari; Rashid, Mohammad; Khodakovskaya, Mariya V. (Frontiers in Plant Science, 2023)
Though still in its infancy, the use of nanotechnology has shown promise for improving and enhancing agriculture: nanoparticles (NP) offer the potential solution to depleted and dry soils, a method for the controlled release of agrochemicals, and offer an easier means of gene editing in plants. Due to the continued growth of the global population, it is undeniable that our agricultural systems and practices will need to become more efficient in the very near future. However, this new technology comes with significant worry regarding environmental contamination. NP applied to soils could wash into aquifers and contaminate drinking water, or NP applied to food crops may carry into the end product and contaminate our food supply. These are valid concerns that are not likely to be fully answered in the immediate future due to the complexity of soil-NP interactions and other confounding variables. Therefore, it is obviously preferred that NP used outdoors at this early stage be biodegradable, non-toxic, cost-effective, and sustainably manufactured. Fortunately, there are many different biologically derived, cost-efficient, and biocompatible polymers that are suitable for agricultural applications. In this mini-review, we discuss some promising organic nanomaterials and their potential use for the optimization and enhancement of agricultural practices.